PENGARUH KEBIJAKAN BIMBINGAN TEKNIS TERHADAP KINERJA LEGISLASI DPRD KABUPATEN BANGLI - Komang Tri Putri Andriastuti; Putu Ngurah Suyatna Yasa; I Wayan Wesna Astara (Universitas Warmadewa, 2017)
This research was conducted to determine the effect of bimtek on legislative performance of DPRD of Bangli regency after bimtek. Bimtek which is one form of common perception for the entire DPRD members consisting of various backgrounds in order to carry out their duties and functions well, especially in terms of performance legislation. This research is conducted so that bimtek which is held by using APBD has an optimal impact on DPRD performance. This study uses the analysis tool PLS (Partial Least Square) with a sample of 30 people who are all members of the DPRD of Bangli Regency. The method used in this analysis is a quantitative method reinforced by qualitative analysis to determine the effect or also the relationship between two or more variables. Technique of collecting data using observation, questionnaire, interview, and also data field. The hypothesis of this research is the significant influence between bimtek and legislative performance of Bangli Regency DPRD. The results of this study indicate that bimtek significantly influence the performance of legislative DPRD Bangli regency.